Make 'em laugh [large type] : short-term memories of longtime friends - Reynolds, Debbie; Hannaway, Dorian (HarperLuxe, an imprint of HarperCollins Publishers, 2015)
The beloved Hollywood star and New York Times bestselling author of Unsinkable continues her intimate chat with fans in this entertaining collection of anecdotes, stories, jokes, and random musings from a woman who has seen it all, and done most of it.